2020
DOI: 10.5603/arm.a2020.0161
|View full text |Cite
|
Sign up to set email alerts
|

Study of Genetic Variants in Chromosome 5p15.33 Region in Non-Smoker Lung Cancer Patients

Abstract: Introduction: Genome-wide association studies have identified that genetic polymorphisms in the telomerase reverse transcrip-tase (TERT) and cleft lip and palate transmembrane 1-like (CLPTM1L) genes may play important roles in the development of lung cancer in never smokers. Material and methods: This study was aiming to evaluate the associations between the risk of lung cancer in never smokers and single nucleotide polymorphisms in these genes by Real-Time Taqman assay, in forty lung cancer patients and forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…To this date, several genetic lesions have been reported to have an influence on adenocarcinoma development in never-smoking patients. For example, Mandour et al (56) documented that SNPs within telomerase reverse transcriptase (TERT), cleft lip, and palate transmembrane 1-like (CLPT-M1L) genes can have an important role in the development of adenocarcinoma in never-smokers. In another study Staff et al (57) showed that gene expression profile differs between AD patients who never smoked and those who smoked suggesting a distinct entity of lung adenocarcinomas in those two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this date, several genetic lesions have been reported to have an influence on adenocarcinoma development in never-smoking patients. For example, Mandour et al (56) documented that SNPs within telomerase reverse transcriptase (TERT), cleft lip, and palate transmembrane 1-like (CLPT-M1L) genes can have an important role in the development of adenocarcinoma in never-smokers. In another study Staff et al (57) showed that gene expression profile differs between AD patients who never smoked and those who smoked suggesting a distinct entity of lung adenocarcinomas in those two groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mandour et al. ( 56 ) documented that SNPs within telomerase reverse transcriptase (TERT), cleft lip, and palate transmembrane 1-like (CLPT-M1L) genes can have an important role in the development of adenocarcinoma in never-smokers. In another study Staff et al.…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC is the most common type of LC, and LUAD is the most prevalent subtype of NSCLC 73 . Previous studies 90 have found rs2736100 to be a risk factor associating with increased susceptibility to LC, especially for LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, adjuvant chemotherapy following radical hysterectomy is not a standard treatment yet; if the probability of recurrence following adjuvant chemotherapy could be predicted, this may assist gynecological oncologists in deciding which adjuvant therapy (chemotherapy or radiation therapy) to use. CLPTM1L was first identified in cisplatin resistance ovarian tumor cells, and recent reports noted that genome-wide association studies revealed a correlation between CLPTM1L expression and lung cancer, pancreatic cancer, prostate cancer, bladder cancer, glioma, melanoma, basal cell carcinoma, and cervical cancer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Understanding the function of CLPTM1L in healthy organs or tissues requires further study; however, CLPTM1L has been reported to play a crucial role in fetal development and neonatal survival but is not essential in adult animals (27).…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lip and palate transmembrane protein 1-like protein [CLPTM1L, also known as cisplatin resistance-related protein 9 (CRR9)] has been identified as an overexpressed protein in human ovarian tumor cells resistant to cisplatin (12). CLPTM1L is a protein that is highly expressed in several types of tumor cells, including lung cancer, pancreatic cancer, prostate cancer, bladder cancer, glioma, melanoma, basal cell carcinoma, and cervical cancer (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The expression of CLPTM1L is associated with the apoptosis mechanism and related to the growth of the tumor cells and resistance against chemotherapy (12,23).…”
Section: Introductionmentioning
confidence: 99%